2014
DOI: 10.5367/te.2013.0261
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization and Financial Health in the US Hotel Industry

Abstract: This study examines two main hypotheses regarding the internationalization and financial health of publicly traded US hotels from 1990 to 2010. First, the study hypothesizes that international US hotels are financially healthier than domestic US hotels. The findings support the hypothesis after controlling for other potential confounding factors: a firm's growth opportunity, profitability, size, leverage, capital intensity and economic conditions. Next, the study tests the second hypothesis, that international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
(69 reference statements)
0
5
1
Order By: Relevance
“…For example, we found a positive effect of all internationalization measures on firms' market performance (i.e., Tobin's q) while some of previous researchers found a negative effect of internationalization on firms' market returns (e.g., Collins, 1990). We also found that the effect of internationalization on firms' operational returns depends on the measures of internationalization, while other researchers suggested a positive effect of internationalization on firms' operational returns (e.g., S. Lee et al, 2014).…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…For example, we found a positive effect of all internationalization measures on firms' market performance (i.e., Tobin's q) while some of previous researchers found a negative effect of internationalization on firms' market returns (e.g., Collins, 1990). We also found that the effect of internationalization on firms' operational returns depends on the measures of internationalization, while other researchers suggested a positive effect of internationalization on firms' operational returns (e.g., S. Lee et al, 2014).…”
Section: Discussioncontrasting
confidence: 39%
“…S. Lee (2008) and Tang and Jang (2010) found a U-shaped relationship with a sample of U.S. hotel companies. Later, S. Lee et al (2014) showed that international hotels have better operational performance than domestic hotels in U.S. Regarding the restaurant industry, Singh et al (2003) found a positive relationship between internationalization and firm performance (measured by operating income growth and pretax profitability).…”
Section: Internationalization and Firm Performancementioning
confidence: 99%
“…Different studies have investigated the effect of international decisions in different contexts, including the tourism industry. In fact, many papers noted the positive influence of internationalization and results in terms of different indicators: ROA (Lee et al, 2014a;Menicucci, 2018;Rienda et al, 2020), Tobin's Q (Lee, 2008;Lee et al, 2014b), sales growth (Rienda et al, 2020), and revenue per available room (Higgins & Higgins, 2006;Ismail et al, 2002;Menicucci, 2018;Woo et al, 2019), among others.…”
Section: Internationalization and Performancementioning
confidence: 99%
“…However, debate continues about the better perform of companies in international markets (Woo et al, 2019). Some papers focused on this relationship find a non-linear U-shaped relation (Assaf et al, 2016;Lee et al, 2014a;Woo et al, 2019), finding that firms achieve higher profits by having accumulated international experience and learning, or an inverted U-shaped relationship when chains make too many investments abroad, requiring large financial efforts and negatively impacting their business results (Brida et al, 2016). Notwithstanding the above, following the organizational learning theory -closely linked to the theory of DCs -, the development of knowledge, either by adapting resources and capabilities or by creating new ones, could explain the influence of firm internationalization on performance (Ruigrok & Wagner, 2003).…”
Section: Internationalization and Performancementioning
confidence: 99%
See 1 more Smart Citation